FREQUENCY AND FACTORS ASSOCIATED WITH INJURY TO THE AXILLARY VEIN IN WOMEN THAT UNDERWENT AXILLARY LYMPHADENECTOMY DURING BREAST CANCER SURGICAL TREATMENT - Corrêa, Rafaela Miranda; Hubie, Danila Pinheiro; Ribeiro, Reitan; Linhares, José Clemente; Hatschbach, Sérgio Bruno Bonatto (Mastology, 2017)
Objective: To evaluate which variables are considered risk factors associated with injury to the axillary vein during lymphadenectomy in the surgical treatment of breast cancer patients. Methods: Retrospective study performed through the electronic record analysis of 1,007 patients who underwent axillary lymph node dissection at Hospital Erasto Gaertner, from January 2010 to December 2014. We assessed the following risk factors using a standard questionnaire: age, body mass index (BMI), presence of palpable axillary metastasis in the clinical examination, sentinel lymph node pre-lymphadenectomy, presence of axillary metastasis in the perioperative period, size of metastasis and if it was adhered to axillary vessels, presence of pectoralis muscle invasion, resection of the pectoralis minor muscle, axillary incision separated from breast incision, prior radiotherapy, neoadjuvant chemotherapy, and pre and postoperative staging. For each patient who presented injury to the axillary vein, we paired them with two homogeneous controls (age, BMI, preoperative staging, surgical proposal, and neoadjuvant treatment). Results: Thirteen patients had injury to the axillary vein. In the perioperative evaluation, in most of them, the axilla was positive in the injury group (10 cases = 76.9%) and control group (12 cases = 46.1%), and it was adhered to axillary vessels in 10 cases in the injury group (76.9%) and 7 in the control group (26.9%). Conclusion: In this study, the presence of axillary metastasis in the perioperative evaluation, as well as that adhered to the axillary vessels, is associated with an increased risk of injury to the axillary vein during lymphadenectomy.